The family circumstances and wellbeing of Indigenous and non-Indigenous children - Baxter, Jennifer (Australian Institute of Family Studies, 2013)
The health and wellbeing and learning outcomes of Indigenous Australian children have improved over recent years, though Indigenous children continue to be at greater risk of poorer developmental outcomes than non-Indigenous Australian children (Australian Institute of Health and Welfare [AIHW], 2011; Steering Committee for the Review of Government Service Provision, 2011). This chapter provides some insights on how the lives of Indigenous children and non-Indigenous children compare, using data from the Longitudinal Study of Australian Children (LSAC), and presents new information on the differences between these groups of children on a range of indicators of child wellbeing. Throughout these analyses, Indigenous children are those who were identified as being Aboriginal or Torres Strait Islander by their primary carer. The LSAC data cannot provide insights for all Indigenous children, because LSAC is not representative of children living in remote areas of Australia. Nevertheless, these data can help to build up a picture of the lives of Indigenous children in non-remote areas, and allow comparisons to be made between these children and non-Indigenous children (Hunter, 2008). While on many (though not all) indicators of child outcomes, Indigenous children living in more remote areas of Australia do not fare as well as other Indigenous children (e.g., Steering Committee for the Review of Government Service Provision, 2011), it is important to note that the majority of Indigenous children live in non-remote parts of Australia, and so a focus on these children is important.1 A particular strength of LSAC for making comparisons of different groups of children is the availability of extensive information about the families and parents of the children. Families set the scene for children's development, with parental characteristics being useful indicators of children's developmental opportunities. To understand the contexts for the development of Indigenous children, these data are used to provide information about their families, and about the parent or parents with whom they are living at each wave of LSAC. While LSAC is not designed to specifically capture the way in which Indigenous households are structured and function, the extensive family information in LSAC provides some useful insights. More information about Indigenous households can be gained through analyses of data from Footprints in Time: The Longitudinal Study of Indigenous Children (LSIC); but as we wish to compare Indigenous and non-Indigenous children in this analysis, we focus here only on the findings from LSAC. Reflecting on the family circumstances of Indigenous compared to non-Indigenous children is particularly important, as Indigenous adults are themselves more often faced with disadvantage when compared to non-Indigenous adults (AIHW, 2011). This is true in areas of financial wellbeing, employment, education, health, and social and emotional wellbeing. Disentangling the different causes of disadvantage is not explored here, nor are the links between different indicators of disadvantage. The goal of the chapter is to describe the family circumstances of children to help build our understanding of the lives of Indigenous children in non-remote parts of Australia. The circumstances of Indigenous families are likely to influence their children's development. Previous research has clearly identified that compared to non-Indigenous children, Indigenous children are more often faced with risk factors that can be detrimental to the achievement of good developmental outcomes (Daly & Smith, 2005). Certainly the poorer wellbeing of Indigenous children is well documented for Australia (AIHW, 2011; Daly & Smith, 2005; Zubrick, 2004; Zubrick et al., 2004). Further, poorer outcomes for Indigenous children have been shown using LSAC data (e.g., Leigh & Gong, 2009; Ou, Chen, Hillman, & Eastwood, 2010; Priest, Baxter, & Hayes, 2012). Various measures of child wellbeing are explored in this chapter, making use of information from the first four waves of LSAC. Parents' and children's reports are incorporated to gain insights from different perspectives. The sample size for Indigenous children does not allow very comprehensive analyses of these data, but the extent to which the relatively poor outcomes of Indigenous children may be related to their being over-represented in households of lower socio-economic position (SEP) is considered. To summarise, the key research questions explored in this chapter are: •How do the family circumstances of Indigenous and non-Indigenous children compare? •What are the differences between Indigenous and non-Indigenous children in terms of how they are progressing in their physical, social-emotional and cognitive wellbeing? •To what extent does the socio-economic position of families of Indigenous children explain any differences in developmental outcomes? The research questions are explored for children at different ages from 0-1 years through to 10-11 years.
LSAC Annual Statistical Report 2012
Keywords: Child Development; Children -- Outcomes; Culture -- Indigenous; Families; Childhood and child development; Families and relationships; Families; Children; Child Development; Culture; Indigenous; Outcomes; Families and relationships; Childhood and child development